Systemic Therapy for Microsatellite Instability Small Bowel Adenocarcinoma With Mesenteric Vascular Embolism as Initial Symptom: A Case Report - Dong, Zhongyi; Xia, Xiang; Zhang, Zizhen (Frontiers in Medicine, 2021)
Background Small bowel adenocarcinoma are relatively rare tumors of the digestive system. Due to the lack of specific screening methods, patients are often diagnosed at an advanced stage. At present, there is no specific surgical guidance and chemotherapy regimen for small bowel adenocarcinoma. Here, we report a rare small bowel adenocarcinoma case with mesenteric vascular embolization and microsatellite instability, in which palliative surgery combined with chemotherapy and anti-PD-1 therapy resulted in complete remission. Case presentation The patient was a 55-year-old man who was admitted for suspected small bowel adenocarcinoma combined with incomplete ileus, mesenteric vascular occlusion and distant metastasis. We performed palliative surgery to remove adenocarcinoma as well as relieve obstruction. Then according to the pathological and immunohistochemical results (Stage IV and microsatellite instability), we used Xelox regimen combined with anti-PD-1 therapy. In last two years follow up, this patient achieved complete remission. Conclusions The possibility of small intestinal tumor should be considered in patients with mesenteric vascular obstruction. PD-1 blockade is an effective therapy for small bowel adenocarcinoma with microsatellite instability.